Start
Zufällige Seite
Anmelden
Einstellungen
Spenden
Über Wikiversity
Haftungsausschluss
Suchen
Differentialform/Zurückziehen/dxdydz-wdxdydw+cos(xy)dxdzdw-ywdydzdw/Unter (r^2s,t, sin r, e^(st))/Aufgabe/Lösung
Sprache
Beobachten
Bearbeiten
<
Differentialform/Zurückziehen/dxdydz-wdxdydw+cos(xy)dxdzdw-ywdydzdw/Unter (r^2s,t, sin r, e^(st))/Aufgabe
Es ist
d
x
=
d
(
r
2
s
)
=
2
r
s
d
r
+
r
2
d
s
,
{\displaystyle {}dx=d(r^{2}s)=2rsdr+r^{2}ds\,,}
d
y
=
d
t
,
{\displaystyle {}dy=dt\,,}
d
z
=
d
(
sin
r
)
=
cos
r
d
r
{\displaystyle {}dz=d(\sin r)=\cos rdr\,}
und
d
w
=
d
(
e
s
t
)
=
s
e
s
t
d
t
+
t
e
s
t
d
s
.
{\displaystyle {}dw=d(e^{st})=se^{st}dt+te^{st}ds\,.}
Damit ist
φ
∗
τ
=
d
(
r
2
s
)
∧
d
t
∧
d
(
sin
r
)
−
e
s
t
d
(
r
2
s
)
∧
d
t
∧
d
(
e
s
t
)
+
cos
(
r
2
s
t
)
d
(
r
2
s
)
∧
d
(
sin
r
)
∧
d
(
e
s
t
)
−
t
e
s
t
d
t
∧
d
(
sin
r
)
∧
d
(
e
s
t
)
=
r
2
cos
(
r
2
s
t
)
cos
r
d
s
∧
d
t
∧
d
r
−
2
r
s
t
e
s
t
e
s
t
d
r
∧
d
t
∧
d
s
+
r
2
s
e
s
t
cos
r
d
s
∧
d
r
∧
d
t
−
t
2
e
s
t
e
s
t
cos
r
d
t
∧
d
r
∧
d
s
=
(
r
2
cos
r
+
2
r
s
t
e
2
s
t
−
r
2
s
e
s
t
cos
(
r
2
s
t
)
cos
r
−
t
2
e
2
s
t
cos
r
)
d
r
∧
d
s
∧
d
t
{\displaystyle {}{\begin{aligned}\varphi ^{*}\tau &=d(r^{2}s)\wedge dt\wedge d(\sin r)-e^{st}d(r^{2}s)\wedge dt\wedge d(e^{st})\\&\,\,\,\,+\cos(r^{2}st)d(r^{2}s)\wedge d(\sin r)\wedge d(e^{st})-te^{st}dt\wedge d(\sin r)\wedge d(e^{st})\\&=r^{2}\cos(r^{2}st)\cos rds\wedge dt\wedge dr-2rste^{st}e^{st}dr\wedge dt\wedge ds\\&\,\,\,\,+r^{2}se^{st}\cos rds\wedge dr\wedge dt-t^{2}e^{st}e^{st}\cos rdt\wedge dr\wedge ds\\&=(r^{2}\cos r+2rste^{2st}-r^{2}se^{st}\cos(r^{2}st)\cos r-t^{2}e^{2st}\cos r)dr\wedge ds\wedge dt\end{aligned}}}
Zur gelösten Aufgabe